Comparing different reactor configurations for Partial Nitritation/Anammox at low temperatures. (15th September 2015) - Gilbert, Eva M.; Agrawal, Shelesh; Schwartz, Thomas; Horn, Harald; Lackner, Susanne
Abstract: Partial Nitritation/Anammox (PN/A) is a well-established technology for side-stream nitrogen removal from highly concentrated, warm wastewaters. The focus has now shifted to weakly concentrated municipal wastewaters with much lower concentrations and temperatures. The major challenge is the temperature, which ranges from moderate 20 °C in summer to cold 10 °C in winter. For this study, the most frequently used configurations for side-stream applications were exposed to a slow temperature reduction from 20 °C to 10 °C to simulate a realistic temperature gradient. To evaluate the behavior of the different biomasses based on their properties, four lab reactors were operated in two different configurations. Synthetic wastewater was used to avoid side effects of heterotrophic growth. Differences in the response of the different reactor systems to this temperature gradient clearly indicated, that the geometry of the biomass has a major impact on the overall PN/A performance at low temperatures: While anammox activity in suspended biomass suffered already at 15 °C, it persevered in granular biomass as well as in biofilms on carriers for temperatures down to <13 °C. Further, anammox activity in thicker biofilms was less affected than in thinner biofilms and even adaption to low temperatures was observed. Graphical abstract: Highlights: Operation of 4 different PN/A reactors over a temperature gradient of 20° to 10 °C. Thicker biofilms show better performance and less nitrite accumulation. Biofilms (MBBR) retain more anammox biomass. Microbial community in MBBR more stable than in SBR.